Імунопатогенез інфекційного реактивного артриту на тлі активованих облігатних інфекцій (Chlamydia trachomatis та Епштейна-Барр вірус), тактика ведення хворих - Ломіковська, Марта Павлівна; Lomikovska, M.P. (Харків : Харківський національний університет імені В.Н. Каразіна, 2021)
Lomikovska M.P. Immunopathogenesis of infectious reactive arthritis in the background of activated obligate infections (Chlamydia trachomatis and Epstein-Barr virus), patient surveillance. - As manuscript. The thesis for the scientific degree of the candidate of medical sciences in specialty 14.03.08 – Immunology and Allergology. – Danylo Halytsky Lviv National Medical University, V. N. Karazin Kharkiv National University, Kharkiv, 2021. The thesis is dedicated to the improvement of the efficiency of treatment and forecasting of the risks of transformation of reactive arthritis (ReA) into rheumatoid arthritis (RA) through the study of the peculiarities of immunopathogenesis in the background of Chlamydia trachomatis (C. trachomatis) and Epstein-Barr virus (EBV). The rate of activity of the inflammatory process under the DAREA index was higher in patients with RеА with combined infection as compared to the group of patients with RеА with C. trachomatis (p<0,05). Molecular and genetic studies have been established: the detection of the DNA of C. trachomatis (in blood serum and in the urinogenital scraping) and Epstein-Barr virus (in blood, saliva, mucous membrane of the posterior pharyngeal wall scraping) as well as specific molecules of immunoglobulin М and immunoglobulin G (IgМ, IgG) to causative antigens.
Immunopathogenesis of infectious reactive arthritis in the background of activated obligate infections (Chlamydia trachomatis and Epstein-Barr virus), patient surveillance
Дисертаційна робота присвячена підвищенню ефективності лікування та прогнозування ризиків трансформації реактивного артриту (РеА) у ревматоїдний артрит (РА) шляхом вивчення особливостей імунопатогенезу РеА на тлі хламідійної і Епштейна-Барр вірусної (ВЕБ) інфекцій. Встановлено клінічні особливості перебігу РеА за індексом DAREA (p<0,05). Визначено молекулярно-генетичні та імунологічні особливості: зниження кількості Т-цитотоксичних лімфоцитів, NK-клітин та збільшення В-лімфоцитів (p<0,05), підвищення рівня miR146a, miR155 (p<0,05), підвищення рівня TNF-α, ІЛ-17, ІЛ-22, ІЛ-23, ІФН-γ, зниження ІЛ-10 (p<0,05), підвищення рівня продуктів глікації (p<0,01). Запропоновано математичну модель прогнозування ризику трансформації РеА в РА.
Keywords: реактивний артрит; Chlamydia trachomatis; Епштейна-Барр вірус; ревматоїдний артрит; лімфоцити; цитокіни; miR155; miR146а; BART 13; BART 15; TLR9; AGE; імуномодулююча терапія; reactive arthritis; Chlamydia trachomatis; Epstein-Barr virus; rheumatoid arthritis; lymphocytes; cytokines; immunomodulatory therapy